PENERAPAN METODE DISKUSI MELALUI PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN PEMAHAMAN MAHASISWA PADA PEMBELAJARAN USHUL FIKIH MAHASISWA EKONOMI SYARIAH - Sahid Dwi Saputra; M. Maimun Haki Al Arif; Ahmad Khoirul Mustamir (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the effectiveness of applying the discussion method to enhance the understanding of Islamic Economics students in learning Ushul Fiqh. A descriptive qualitative approach was employed, involving classroom observations, in-depth interviews with lecturers and students, as well as documentation analysis related to the discussion-based learning process. The findings indicate that the discussion method significantly contributes to improving students’ comprehension, particularly regarding foundational Ushul Fiqh concepts such as sources of Islamic law, legal maxims, and methods of legal reasoning. Students not only became more active and confident in expressing their ideas but also demonstrated improved analytical abilities through argumentation, clarification, and collaborative inquiry. The discussion activities further enabled students to connect Ushul Fiqh theories with contemporary economic issues, resulting in more contextual and applicable understanding. Although challenges such as unequal participation and varied levels of academic readiness were identified, these issues can be effectively addressed through proper instructional facilitation. Overall, the study affirms that the discussion method is an effective, collaborative, and pedagogically relevant strategy for enhancing the quality of Ushul Fiqh learning among Islamic Economics students.